Critical Digital Pedagogy’s Framework: Lecturer’s Voices to Analysis the Incorporation of Discord Tool in Higher Education - Lestari R, Kenny Shania; Widiati, Utami; Maria Ivone, francisca (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
Critical pedagogy can be reflected in the situation when the learners become social transformers of their community and world, and when they critically construct knowledge. The prior researchers s only evaluated discrepancies in gender and age. Freire and Brown's framework also verified the feasibility and reliability of implementing CDP. However, general skills and unspecific digital tools drove the reader's bias and ambiguity. Consequently, the purposes of the study aim to connect previous topics in different contexts, addressing the gap and providing a critical analysis. Especially, English lectures in certain skills and specific digital tools would be needed to know critical pedagogy's intentional implementation or unintentional presence in the ELT realm. Three concerns were highlighted to guide the researchers to do the research; the essential aspect of pedagogy that has and has not been involved yet in online learning and the factors of age and gender that might influence the learning. Th researchers s used qualitative method, especially observation and questionnaire instruments to get the data of the incorporation of the Discord tool of critical pedagogy in the higher education domain. The findings reveals that the implementation a critical pedagogy of Discord tool and the discrepancies of age and gender that influence the online meeting.